2008
DOI: 10.1007/s10658-007-9237-2
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from clubroots: alterations in host roots and hormone homeostasis caused by Plasmodiophora brassicae

Abstract: The clubroot disease of cruciferous crops is caused by an obligate biotrophic protist, Plasmodiophora brassicae. The disease is characterized by the development of large root galls accompanied by changes in source-sink relations and the hormonal balance within the plant. Since the disease is difficult to control, it is of high economic interest to understand the events leading to gall formation. In this review we will give an overview on the current knowledge of changes brought about in the host root by this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…Several studies indicate that there is an increase in cytokinins at late time points during root gall formation (Devos et al 2006;Siemens et al 2006;Ludwig-Müller and Schuller 2008). The current microarray results confirm the involvement of cytokinins at the early infection stage.…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencesupporting
confidence: 85%
See 4 more Smart Citations
“…Several studies indicate that there is an increase in cytokinins at late time points during root gall formation (Devos et al 2006;Siemens et al 2006;Ludwig-Müller and Schuller 2008). The current microarray results confirm the involvement of cytokinins at the early infection stage.…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencesupporting
confidence: 85%
“…The jar1 mutant was more sensitive to clubroot infection, according to Siemens et al (2002), and was also confirmed to be susceptible to the Australian population of P. brassicae. Induction of one lipoxygenase gene at 23 DAI has been shown by Siemens et al (2006), indicating a potential role for jasmonic acid during gall development (Ludwig-Müller and Schuller 2008). In contrast, several genes involved in the ethylene pathway (1-aminocyclopropane-1-carboxylate synthase 2 and a putative ethylene receptor, ETR2) were downregulated at the early time point.…”
Section: Genes Involved In Hormone Synthesis Signalling and Defencementioning
confidence: 90%
See 3 more Smart Citations